1995
DOI: 10.1093/bja/74.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and sequelae of very low-dose suxamethonium for nasal intubation

Abstract: We have studied the effectiveness and sequelae of low-dose suxamethonium in 60 day-case oral surgery patients requiring nasal intubation. Anaesthesia was induced with propofol and alfentanil; 60 patients were allocated randomly to three groups of 20 patients and received no suxamethonium, suxamethonium 0.25 mg kg-1 or 0.5 mg kg-1. All patients received i.v. fentanyl and diclofenac 100 mg rectally for analgesia. Good intubating conditions were produced in all 20 patients receiving suxamethonium 0.25 mg kg-1, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 15 publications
(17 reference statements)
0
25
0
Order By: Relevance
“…Intravenous succinylcholine, in a dose of small as 0.1 mg/kg had been found to be reliable in the treatment of laryngeal spasm. 6 Although succinylcholine has commonly been employed in low doses in combination with other induction agents for the insertion of LMAs, potential problems such as masseter muscle spasm, prolonged apnoea, myalgia, hyperkalemia and inadvertent administration to patients with pseudocholinesterase deficiency or malignant hyperthermia may occur. 14,15 These were not problems that were encountered in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravenous succinylcholine, in a dose of small as 0.1 mg/kg had been found to be reliable in the treatment of laryngeal spasm. 6 Although succinylcholine has commonly been employed in low doses in combination with other induction agents for the insertion of LMAs, potential problems such as masseter muscle spasm, prolonged apnoea, myalgia, hyperkalemia and inadvertent administration to patients with pseudocholinesterase deficiency or malignant hyperthermia may occur. 14,15 These were not problems that were encountered in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Nimmo and colleagues suggested that this adverse reactions can be avoided by reducing the doses of succinylcholine substantially. 6 Previous studies had proven the usefulness of mini-dose succinylcholine (0.1mg/kg) for insertion of LMA without significant patient reaction under propofol anaesthesia in patients coming for elective short surgical procedures. 6 In our study we have compared two small doses of succinylcholine (0.1mg/kg and 0.2mg/kg) to assess the ease of LMA insertion.…”
Section: Introductionmentioning
confidence: 99%
“…[41012] Stewart et al . [11] reported that 26 (96%) of 27 patients receiving 1.5 mg/ kg succinylcholine and 30 (94%) of 32 patients receiving 0.5 mg/kg had acceptable intubating conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Overall insertion condition was assessed by modified scheme of grading of intubation conditions by Lund and Stovner 4 . Incidence of gagging or coughing on insertion was scored on a four point scale according to Nimmo and collegues 5 . Incidence of laryngospasm and other complication was also noted.…”
Section: Methodsmentioning
confidence: 99%